2013
DOI: 10.1016/j.cell.2013.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cells Derived by Somatic Cell Nuclear Transfer

Abstract: We wish to correct a number of figure-related and typographical errors that appeared in the article above. None of these errors affect the conclusions of the paper.In Figures 2F and S5 (upper-right), we presented two phase-contrast photos of fields of cells, correctly labeled as SCNT-derived hESO-NT1 and IVF-derived hESO-7, respectively. These images are the same fields of cells shown in the top two images of Figure 6D; however, in Figure 6D, we inadvertently switched the labels on the images. This re-use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
220
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(229 citation statements)
references
References 0 publications
2
220
0
7
Order By: Relevance
“…Research gamete donors were financially compensated for their time, effort, discomfort, and inconvenience associated with the donation process at rates similar to donors whose gametes were used for reproductive purposes. This specific IRB protocol was first approved in 2011 and then reviewed annually with modifications allowing the development, evaluation and testing, in vitro, of novel mitochondrial replacement techniques (see Data S1) (Kang et al, 2016;Ma et al, 2015;Tachibana et al, 2013a;Tachibana et al, 2013b).…”
Section: Gamete Donationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research gamete donors were financially compensated for their time, effort, discomfort, and inconvenience associated with the donation process at rates similar to donors whose gametes were used for reproductive purposes. This specific IRB protocol was first approved in 2011 and then reviewed annually with modifications allowing the development, evaluation and testing, in vitro, of novel mitochondrial replacement techniques (see Data S1) (Kang et al, 2016;Ma et al, 2015;Tachibana et al, 2013a;Tachibana et al, 2013b).…”
Section: Gamete Donationmentioning
confidence: 99%
“…We previously demonstrated that interphase nuclei of skin fibroblasts transplanted into enucleated human MII oocytes (cytoplasts) undergo rapid remodeling and cell cycle reprogramming resulting in the formation of oocyte-like MII-arrested spindles Tachibana et al, 2013a). We determined that the residual meiotic activity in cytoplasts capable of forming de novo MII spindles is critical for reprogramming and subsequent embryonic development following somatic cell nuclear transfer (SCNT).…”
Section: Introductionmentioning
confidence: 99%
“…The very recent paper published by Mitalipov's groups confirmed that this is true [5]. In these experiments the oocytes from paid donors were used and some minor, but probably very essential modifications, were introduced into their NT scheme.…”
Section: Inconsistent Resultsmentioning
confidence: 87%
“…In fact, both these treatments were already used in animal NT experiments and improved their efficiency [9]. In general, the NT scheme has been perfected in previous experiments performed by this group and some other technical details can be found in a given paper [5]. Taken together, the efficiency of a given NT scheme was quite high and this was confirmed by a very good embryonic development and high efficiency when ESC lines were established from them.…”
Section: Inconsistent Resultsmentioning
confidence: 92%
“…The two major approaches, somatic cell nuclear transfer (SCNT) and reprogramming of somatic cells into induced PSCs (iPSCs), have been successfully applied to mouse and human cells [12][13][14][15]. There have been reports on successful rescue of disease phenotypes in some mouse models, such as mice carrying mutations in Crygc [16], Lrrk2 [17], and Bcl11a [18], by combing somatic cell reprogramming and gene correction technologies.…”
Section: Introductionmentioning
confidence: 99%